The influence of job search stress on college students’ addictive social media use: Seeking of social support and perceived social support as serial mediators and sense of coherence as a moderator - Mao, Eric (Zeqing); Zhao, Lishou (Frontiers in Psychology, 2023)
Resulting from an enlarged number of graduating college students and shrinkage of work opportunities, stress in relation to job search and employment is becoming an increasingly noticeable issue in China. Previous psychiatry research has suggested that social support can be conducive to reducing stress from multiple sources, while the effectiveness hinges on whether it is actually recognized and perceived by the recipients. The prevalence of social media has greatly facilitated the communication and exchange of social support information. However, they can also lead to overuse and addiction problems. This study aims to investigate how job search stress affects graduating college students’ social media addiction severity using a serial mediation model and test the potential moderation effect of sense of coherence. Based on a sample of graduating college students (n = 144), our findings point out a significant pathway for the impacts of stress sequentially through seeking of social support and perceived social support. Furthermore, job search stress seems to have pronounced effects on the psychological need for social support only at low- and mid-levels of sense of coherence.